XML data schemas and scalable vector graphics format for the sea level observations - Marozas, Leonardas; Paršeliūnas, Eimuntas; Urbonas, Saulius (Geodesy and Cartography, 2012)
XML (Extended Markup Language) Data Schemas as the format for information exchange in graphical SVG (Scalable Vector Graphics) format is presented. SVG format is a language for two‐dimensional graphics and is based on XML. It is the advanced version of previous data exchange format TGX (Tide Gauge Independent Exchange Format), which contains the plain ASCII data. SVG graphics are formatted from sea level observations data at ESEAS station KLPD. Comparing with similar CGM (Computer Graphics Metafile) format, SVG has its advantages of being based on XML. XML Data Schemas, in addition, add a header information about the marine measurements site, sensors and any additional necessary information. The correct header formation and the advantages of such data exchange format are analysed. Header is important for an exchange between different sites from different countries so as it would be information standardisation. Visual appearance of the SVG file, the source, headers and formation of the file in script are described too. First published online: 03 Aug 2012